Consistent and chronic cochlear implant use partially reverses cortical effects of single sided deafness in children - Hyo-Jeong Lee (Nature Portfolio, 2020)
Abstract Potentially neuroprotective effects of CI use were studied in 22 children with single sided deafness (SSD). Auditory-evoked EEG confirmed strengthened representation of the intact ear in the ipsilateral auditory cortex at initial CI activation in children with early-onset SSD (n = 15) and late-onset SSD occurring suddenly in later childhood/adolescence (n = 7). In early-onset SSD, representation of the hearing ear decreased with chronic CI experience and expected lateralization to the contralateral auditory cortex from the CI increased with longer daily CI use. In late-onset SSD, abnormally high activity from the intact ear in the ipsilateral cortex reduced, but responses from the deaf ear weakened despite CI use. Results suggest that: (1) cortical reorganization driven by unilateral hearing can occur throughout childhood; (2) chronic and consistent CI use can partially reverse these effects; and (3) CI use may not protect children with late-onset SSD from ongoing deterioration of pathways from the deaf ear.